2019
DOI: 10.1016/j.jacbts.2019.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Post-Infarction Cardiac Structure and Function via Long-Term Oral Formyl Peptide Receptor Agonist Treatment

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 42 publications
4
41
0
Order By: Relevance
“…Mice deficient in individual Fprs show not only an increased susceptibility to microbial infections but also a delayed tissue repair [7,24,25]. In addition, a recent study has elegantly demonstrated that activation of FPRs improves cardiac function in a post myocardial infarction model [26], suggesting an anti-inflammatory/pro-resolving role of FPR agonists.…”
Section: Introductionmentioning
confidence: 99%
“…Mice deficient in individual Fprs show not only an increased susceptibility to microbial infections but also a delayed tissue repair [7,24,25]. In addition, a recent study has elegantly demonstrated that activation of FPRs improves cardiac function in a post myocardial infarction model [26], suggesting an anti-inflammatory/pro-resolving role of FPR agonists.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the agonists examined, the signals generated by FPR2 mediate primarily pro-inflammatoryactivities, yet anti-inflammatory activities have also been described [8][9][10][11]. Based on the important roles of FPR2 in host defense and regulation of inflammation, this GPCR has been considered as a promising drug target for inflammatory conditions including cardiovascular diseases [12,13]. FPR2 transduces signaling primarily through heterotrimeric Gi/o proteins and the dissociated G subunits trigger activation of phospholipase C (PLC) associated with an increase in intracellular Ca 2+ [5,7].…”
mentioning
confidence: 99%
“…In this issue of JACC: Basic to Translational Science , García et al. (2) explore the use of formyl peptide receptor (FPR) agonist, Compound 43 (Cmpd43), as a therapeutic agent that targets pattern recognition receptors to promote a more favorable immunological response and improve infarct healing.…”
mentioning
confidence: 99%
“…García et al. (2) focus on modulating recruited monocytes toward a proresolution phenotype to expedite tissue healing with Cmpd43—a dual FPR1/FPR2 agonist (4). Using in vitro assays, the authors first determined the role of FPR agonism by Cmpd43 on key macrophage functions of chemotaxis, phagocytosis, and cytokine release via receptors FPR1 and FPR2 separately.…”
mentioning
confidence: 99%
See 1 more Smart Citation